Paranoid of Android. - Tivnan, Tom (Bookseller, 2010)
The article discusses the results of a study released by GfK Group in Great Britain in 2010 concerning the sales performance of smartphones. There has been an increase in the sales performance of smartphones that feature the Google Android operating system (OS). The article also offers information on the open source system of Google Inc. and the closed system of Apple Inc.